The Legacy Effect in Treating Hypercholesterolemia. (July 2020) - Kostis, John B.; Shetty, Mrinali; Chowdhury, Yuvraj Singh; Kostis, William J.
Background: The duration of randomized controlled clinical trials usually is approximately 3 to 5 years although hypercholesterolemia and other risk factors for atherosclerotic cardiovascular disease (ASCVD) are lifelong conditions. Objectives: The legacy effect, defined as the persistence of benefit of pharmacologic interventions in clinical trials after the end of the randomized phase when all participants receive active therapy, is used to examine the long-term benefit. We summarize the evidence for the existence of the legacy effect as it pertains to hypercholesterolemia, describe underlying mechanisms, and discuss its relevance to clinical practice. Methods: We examined all published (n = 13) randomized clinical trials of lipid-lowering agents compared to placebo or usual care with follow-up after the randomized phase for the presence or absence of a legacy effect. Results: A legacy effect was demonstrated in all studies. The current US and European guidelines recommend treatment with high-intensity statins for patients with manifest ASCVD and that individualized approach be used for primary prevention. Conclusion: The legacy effect results in significant long-term clinical benefits by preventing fatal and nonfatal events. This implies that early therapy would result in lower event rates. Long-term follow-up should be a part of clinical trial design in order to evaluate the presence or absence of a legacy effect.